Outcomes of a Provincial Pilot Program to Reduce Unnecessary Urine Culturing and Antibiotic Overuse in Long-term Care. (4th October 2017) - Brown, Kevin; Chambers, Andrea; Leung, Valerie; Langford, Bradley; Quirk, Jacquelyn; Garber, Gary
Abstract: Background: Antibiotics are frequently prescribed for long-term care residents with asymptomatic bacteriuria, for which there is no indication. In order to help reduce unnecessary urine culturing and concomitant antibiotic use, C. difficile infection, and antibiotic resistance, Public Health Ontario (PHO) developed a multi-component organizational change program. The program focuses on five practice changes, recommends nine implementation strategies that have been linked to barriers, and includes an implementation planning process. Methods: A purposive sampling strategy was used to recruit 12 long-term care homes (LTCHs) in the province of Ontario, Canada. LTCHs worked with PHO staff to implement the program over a 4-month period in mid-2016. The outcome evaluation compared rates of urine cultures sent, total antibiotics, and urinary antibiotics (ciprofloxacin, nitrofurantoin, TMP/SMX, and fosfomycin) per 1, 000 resident days before and after the implementation phase. A Poisson regression model adjusting for time-trends, seasonality and controlling for autocorrelation, was used. Results: Of the 12 LTCHs recruited, as of May 2017, 9 LTCHs provided data, totaling 106 facility-months. During the pre-implementation phase, inter-facility variation in urine culturing rates (mean = 2.4, inter-decile range [IDR] = 4.3), total antibiotic use (median = 3.2, IDR = 5.5), and urinary antibiotic use (median = 1.2, IDR = 2.2), were large (Figure 1). Comparing the post-implementation period to the pre-implementation period, we observed a 31% adjusted decline in urine culturing (incidence rate ration [IRR] = 0.69, 95% CI: 0.51 to 0.94, Figure 2), a 65% adjusted decline in total antibiotic use (IRR = 0.35, 95% CI: 0.13 to 0.92), and a 38% adjusted decline in urinary antibiotic use (IRR = 0.62, 95% CI: 0.23 to 1.68) across the participating facilities. Conclusion: While there was variation in baseline urine culturing rates and antibiotic use across LTCHs, preliminary data indicate that these outcomes declined in a relatively short time period following implementation of an organizational change program. Plans to expand the program to the provinces 600 LTCHs could prioritize facilities with high baseline urine culturing rates. Disclosures: All authors: No reported disclosures.